REKAYASA MEMPERINDAH TUBUH DALAM TINJAUAN MEDIS DAN FIKIH - Asnan Purba (Universitas Darussalam Gontor, 2020)
Every human being especially woman tends to be happy for beauty that is related to the feelings. Many people to look beautiful, they shape the body by medical surgery to beautify her face, sharpen their nose, and change the color of her skin. It is urgen to know how Islam regards this practice. Therefore the paper aims to describe and explore the engineering of body beauty in medical and fiqh analysis. Methodology used for the study is qualitative by using content analysis to analyse Islamic and medical view of the engineering of body beauty. The finding of study is that beautification of the body is permissible in Islamic law as long as it does not change the form of Allah’s creation and does not cause harm in humans which causes disability, illness and others. Regarding disgrace and disability therefore changing its form is permissible in Islam because of natural disability or disgrace and because of certain problems that cause defects in one of the organs of the body. Can be done in a compilation of Islamic law for care or treatment for someone.